The Laser Transformation Hardening Mechanism of High Speed Steel W6Mo5Cr4V2 - 刘宁 邓宗钢 胡镇华 崔昆 孔捷 程本培 (中国科学通报：英文版, 1994)
The application of laser surface melting in the laser heat treatment of high speedsteel causes low hardness, so the subsequent quenching and tempering processesare needed. And by means of transformation hardening techniques, ultrahighhardness >HV1000 can be obtained.In this case, the subsequent quenching pro-cess can be saved, and the wear and scuffing resistances can be considerably im-proved. However, the laser transformation hardening mechanism has not beenunderstood clearly. The laser transformation hardening mechanism of high speedsteel W6Mo5Cr4V2 has been studied in the present note by TEM and X-ray diffractionmethod in order to provide a theoretical basis for application.